The Influence of Influencer Marketing in Increasing Brand Awareness and Sales for SMEs - Agustian, Kresnawidiansyah; Hidayat, Rachmat; Zen, Agustian; Sekarini, Ratih Ayu; Malik, Aulia Januar (PT. LITERASI SAINS NUSANTARA, 2023)
In the ever-evolving digital era, marketing through social media has become one of the most effective tools to promote products and services. One of the latest marketing trends that is emerging is the use of influencers in marketing strategies. This study aims to investigate the effect of influencer marketing on increasing brand awareness and sales for SMEs. The technique applied is a qualitative literature analysis with an emphasis on in-depth understanding of the subject over the period from 2012 to 2023. The results of this study indicate that influencer marketing has great potential to provide significant benefits to SMEs in their endeavours to reach their target market, expand brand awareness, and increase sales. In an ever-changing digital world, influencers hold unique appeal as a source of influence that can connect brands with relevant and engaged audiences.